2015
DOI: 10.1063/1.4922314
|View full text |Cite
|
Sign up to set email alerts
|

Self-propulsion of a counter-rotating cylinder pair in a viscous fluid

Abstract: We study a self-propelling pair of steadily counter-rotating cylinders in simulations of a two-dimensional viscous fluid. We find two strikingly, opposite directions for the motion of the pair that is characterized by its width and rotational Reynolds number. At low Reynolds numbers and large widths, the cylinder pair moves similarly to an inviscid point vortex pair, while at higher Reynolds numbers and smaller widths, the pair moves in the opposite direction through a jet-like propulsion mechanism. Increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Increase of both the center velocity and the jet thrust due to the widening gap are also shown in a previous study (Figures 5 and 6 in Ref. 13). One implication of this result is the reversal of the overall thrust direction for the cylinder pair.…”
Section: Flow Behaviorsupporting
confidence: 85%
See 1 more Smart Citation
“…Increase of both the center velocity and the jet thrust due to the widening gap are also shown in a previous study (Figures 5 and 6 in Ref. 13). One implication of this result is the reversal of the overall thrust direction for the cylinder pair.…”
Section: Flow Behaviorsupporting
confidence: 85%
“…Van Rees et al [13] performed a very detailed study of the self-propulsion of the counter-rotating cylinder pair in stationary fluid. Although they imposed no free stream flow velocity, their study also revealed the two different mechanisms of self-propulsion, depending on the distance between the cylinders and the rotational speed.…”
Section: Introductionmentioning
confidence: 99%
“…22,28,29 A number of studies have relied on this technique for coupling simulations of self-propelled swimmers with machine learning algorithms, 30 and for design-optimization of swimmer morphology and kinematics. [31][32][33][34] These studies demonstrate the capability of the penalization algorithm to handle multiple, complex, and deforming geometries with relative ease. Nonetheless, these studies have not overcome the difficulty of determining pointwise forces exerted on a solid surface.…”
mentioning
confidence: 79%
“…Beyond this work, we believe that the simplicity of the 3D cylinder pair, both in its geometry and actuation, makes it an attractive model system for both theoretical studies and practical applications of low Reynolds number applications. Different extensions can be easily examined, such as investigating unsteady gaits in the inertial regime 13 , employing three or more cylinders and analyzing their optimal configuration in 3D, and broadening to applications beyond locomotion, by using the flow induced by the counter-rotating cylinders for sensing and mixing.…”
Section: Discussionmentioning
confidence: 99%
“…By changing the reference frame, this result can also be found in the century-old work by Jeffery 12 . The behavior of the counter-rotating cylinder pair in Reynolds numbers of O(10)-O(100) was undertaken in van Rees, Novati, and Koumoutsakos 13 by numerically solving the Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%